Educational actions in the prevention of arterial hypertension in workers - Zélia Maria de Sousa Araújo Santos; Hélder de Pádua Lima (Rev Rene)
This is a participative research aiming to evaluate the life style changes occurred with fourteen workers concerning the prevention of the risk factors of SAH, with the accomplishment of five educational meetings. The data was collected, through interviews. The results were organized in empirical categories. Among the participants, eleven were aged 21 to 44; ten of them were medium brown and one was black. The workers seemed to understand a little about the risk factors of SAH and its prevention. For such people, having a healthy life style, consisted in practicing physical exercises to manage with stress, to eat healthy food, and to avoid addiction. The meetings changed the life style of thirteen citizens, once they prevented and/or controlled the factors of environmental risks and, as a result, the risk of SAH in themselves, in members of their families as well as in other people with whom they have any relationship.